22-3x=-4(4x+2)-4(-3-3x)

Simple and best practice solution for 22-3x=-4(4x+2)-4(-3-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22-3x=-4(4x+2)-4(-3-3x) equation:


Simplifying
22 + -3x = -4(4x + 2) + -4(-3 + -3x)

Reorder the terms:
22 + -3x = -4(2 + 4x) + -4(-3 + -3x)
22 + -3x = (2 * -4 + 4x * -4) + -4(-3 + -3x)
22 + -3x = (-8 + -16x) + -4(-3 + -3x)
22 + -3x = -8 + -16x + (-3 * -4 + -3x * -4)
22 + -3x = -8 + -16x + (12 + 12x)

Reorder the terms:
22 + -3x = -8 + 12 + -16x + 12x

Combine like terms: -8 + 12 = 4
22 + -3x = 4 + -16x + 12x

Combine like terms: -16x + 12x = -4x
22 + -3x = 4 + -4x

Solving
22 + -3x = 4 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
22 + -3x + 4x = 4 + -4x + 4x

Combine like terms: -3x + 4x = 1x
22 + 1x = 4 + -4x + 4x

Combine like terms: -4x + 4x = 0
22 + 1x = 4 + 0
22 + 1x = 4

Add '-22' to each side of the equation.
22 + -22 + 1x = 4 + -22

Combine like terms: 22 + -22 = 0
0 + 1x = 4 + -22
1x = 4 + -22

Combine like terms: 4 + -22 = -18
1x = -18

Divide each side by '1'.
x = -18

Simplifying
x = -18

See similar equations:

| X=-5b+12 | | 8(x+62)=10(x+5) | | 29-(-5)=-2x+13-x | | 4+6x=3(2x+3) | | x-(6+3x)= | | 2x+2+2x+2= | | -7+(9x+2)=-(6x+3)-9 | | 5m+5=-100 | | 15x=2x^2+28 | | 2x+64.2=90 | | X=4(59/13)-20 | | 3y+21=3y-6 | | y=5lny | | -6y-5(-3y-5)=8-7(1-y) | | 3logx(5)+logx(3)=7 | | 11-3x=5x+8-7x | | 14x+69=0 | | 0.3(x+40)-0.06(x-60)=6 | | 5(2-d)=6(d-5)+6d | | 8(-2-7)=28+5x | | -20.5=w/6-1.3 | | 3/2t=2 | | 0.1(x+60)-0.02(x-10)=10.2 | | 3.2x+4=-5.7 | | -24x=168 | | 50+x=y | | 55-x=36 | | 500+20x=300+35x | | -10x+8=0 | | X+50=z | | 0.1x+6-0.02x-0.2=10.2 | | 5(x+7)-(2x-3)=3 |

Equations solver categories